(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2024)
The environmental crisis is an extremely complex problem for its causes are many and diverse. An effective solution to this crisis will require a concerted effort among various academic disciplines and socio-economic institutions. This kind of undertaking, however, is immensely challenging given the lack of a unifying framework that is acceptable to everyone. One preliminary step is to have a clear conception of the kinds of causes that have brought about the crisis to determine the roles the various academic disciplines and socio-economic institutions can play in the management and eventually the resolution of the crisis. This article provides one conception of how this preliminary step can be done but with a special focus on the role of philosophy. The main objective is to clarify the aspect in the management of the crisis in which philosophy can make a substantial contribution.